ESRA19-0146 Efficacy of ultrasound-guided radiofrequency ablation for genicular nerve in patients with chronic knee pain after total knee arthroplasty. (30th August 2019) - Yoshimura, N; Yamaguchi, S; Tanabe, K; Iida, H
Abstract : Background and aims: Despite a good outcome for many patients, approximately 20% of patients experience chronic pain after total knee arthroplasty (TKA). Radiofrequency ablation (RFA) for genicular nerve has recently gained popularity as an intervention for chronic knee pain in patients who have failed other conservative treatment. In the present study, we aimed to evaluate the efficacy of ultrasound-guided RFA for genicular nerve in patients with chronic knee pain after TKA. Methods: This study included 14 knees of 10 patients with chronic knee pain after TKA. Ultrasound-guided RFA was performed 80°C for 90 seconds. Pain intensity was assessed by Numeric Rating Scale (NRS 0–10) and knee disability was assessed by the Western Ontario McMaster OA Index (WOMAC). Each assessment was observed before procedure (baseline) and at 2, 4, 8, 12 weeks after procedure. All measurement values were expressed as mean ± SD. Outcome measures over time were evaluated using the repeated measurement general linear model. a value of p<0.05 was considered statistically significant. Results: Baseline NRS was 7.1±1, 1, and WOMAC was 76.9±10.3. Significant decrease in pain and significant improvement in knee function were observed at 2 weeks (NRS; 3.9±1.3, WOMAC; 51.6±12.6, p<0.05), 4 weeks (NRS; 4.9±1.5, WOMAC; 51.7±12.4, p<0.05), and 8 weeks (NRS; 5.8±1.1, WOMAC; 53.7±10.8, p<0.05), compared to baseline values. No serious complication was found in any patient. Conclusions: Ultrasound-guided RFA for genicular nerve could be safe and beneficial treatment in the patients with chronic knee pain after TKA.